Membangun Pertanian Ramah Lingkungan Melalui Program Aplikasi PGPR Di Lahan Sawah Kelompok Tani Maju Makmur Desa Kalisat, Kabupaten Jember - Argarisma, Feni; Kustiari, Tanti; Muksin, Muksin (Welfare : Jurnal Pengabdian Masyarakat, 2023)
PGPR is a local microorganism that has an important role in promoting plant growth in an environmentally friendly manner. That’s could to increase plant resistance to pathogenic fungi. Community service activities was carried out at the Maju Makmur farmer group, Kalisat Village, Jember Regency from October to November 2022. The methods of community empowerment are lectures, discussions, method demonstrations. Material was given about the benefits of PGPR, the stages of making PGPR and application techniques to paddy fields. The results of the activity obtained an increase in knowledge and skills in using bamboo root PGPR in corn and celery vegetables. Corn and celery yields showed a tendency to increase the number of kilograms and increase the performance of longer corn. PGPR can play a role as a supporter of environmentally friendly agricultural systems. PGPR for farmer groups can become a joint venture through supply and distribution activities at agricultural shops.